Analisis Rechtspolitiek Menuju Hukum Progresif Di Indonesia - Abdur Rahim; Shepti Maulia; Ikbal Hanafi; Bagus Tegar Awaluddin; Farid Anwar Fuadzi; Fatikha Salsabila (Gapenas Publisher, 2026)
This study aims to analyze the role of rechtspolitiek in promoting the realization of progressive law in Indonesia. The background of this research is based on the high level of public dissatisfaction with law enforcement and the suboptimal performance of the legal system in achieving substantive justice. This study employs a qualitative approach using a library research method, by examining laws and regulations, books, scientific journals, and relevant policy documents. Data analysis is conducted using the interactive model of Matthew B. Miles and A. Michael Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that rechtspolitiek plays a strategic role in shaping a legal system that is responsive, participatory, and oriented toward social justice. However, its implementation still faces various challenges, including resistance to change, rigid bureaucracy, political interests domination, and legal pluralism complexity. Therefore, strengthening progressive legal politics is necessary through regulatory reform, increased public participation, and synergy among government, academics, and civil society. Consequently, progressive law can function as an instrument to achieve substantive justice and public welfare.